Printing of tunable diffractive optical elements on graphene oxide thin-film using femtosecond laser induced photoreduction - Kim, Young-Jin (2018)
We present diffractive optical elements printed on graphene oxide (GO) thin film using femtosecond (fs) laser induced photoreduction process. Graphene oxide is an interesting advanced material as its optical and electrical properties change after laser induced photoreduction to become reduced graphene oxide (rGO). rGO is opaque with good electrical conductivity. Femtosecond laser enables printing of sub-micrometer diffractive optical structure on rGO films which can be used transmission grating and Fresnel lens. The physical dimensions of diffractive optical elements can be tuned by transferring the rGO-GO patterns to a dielectric elastomer actuator (DEA). rGO played a dual role being a compliant electrode to the DEA and as an optical element with low transmittance. Highly transparent DEA substrate ~ tens of μm thickness was used for printing of the desired structures. The diffractive optical elements undergo compression or expansion varied to the designed rGO pattern as the DEA substrate stretched when a voltage is applied. The ease of the printing process and the arbitrary patterning capability of Fs laser induce photoreduction allows the fabrication of highly efficient ultrathin tunable optical components.